2007
DOI: 10.1007/s11199-007-9274-5
|View full text |Cite
|
Sign up to set email alerts
|

Thin-Ideal Media and Women’s Body Dissatisfaction: Prevention using Downward Social Comparisons on Non-Appearance Dimensions

Abstract: Exposure to thin-ideal media has adverse effects on the body satisfaction of women with higher levels of body image disturbance. In a study involving 109 UCLA female undergraduates, we examined the effectiveness of an intervention that was based on downward social comparison theory and the selection of alternative comparison dimensions. All participants had higher levels of body dissatisfaction and viewed pictures of fashion models; the intervention group compared downward with the models on non-appearance dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 72 publications
1
18
0
Order By: Relevance
“…Other studies have suggested that girls and women prompted to make downward comparisons, especially on non-appearance-related dimensions, reported higher body satisfaction and positive mood than those instructed to make upward body comparisons (van den Berg and Thompson 2007). Similarly, an intervention that asked participants to make downward comparisons to models on non-appearance dimensions, such as special talents or important friendships, reported more positive shifts in body image, weight satisfaction, and anxiety related to appearance than did women who simply compared themselves to models (Lew et al 2007). It is possible that interventions designed to lessen the amount of body surveillance may also reduce their tendency to make body comparisons and body shame.…”
Section: Limitations and Implications For Future Researchmentioning
confidence: 95%
“…Other studies have suggested that girls and women prompted to make downward comparisons, especially on non-appearance-related dimensions, reported higher body satisfaction and positive mood than those instructed to make upward body comparisons (van den Berg and Thompson 2007). Similarly, an intervention that asked participants to make downward comparisons to models on non-appearance dimensions, such as special talents or important friendships, reported more positive shifts in body image, weight satisfaction, and anxiety related to appearance than did women who simply compared themselves to models (Lew et al 2007). It is possible that interventions designed to lessen the amount of body surveillance may also reduce their tendency to make body comparisons and body shame.…”
Section: Limitations and Implications For Future Researchmentioning
confidence: 95%
“…Adolescents use their friends as weight referents, and this social comparison is associated with inaccurate weight perception and negative weight related cognitions. Past interventions have been able to buffer the effects of downward weight related social comparison by facilitating non-appearance based comparison (Lew et al, 2007). In areas with disproportionately high rates of obesity, interventions should aim to encourage non-appearance based comparison that is health focused (e.g., physical strength or medically healthy weight).…”
Section: Implications For Interventionmentioning
confidence: 99%
“…For example, Roberts and Good (2010) found that women high in the personality trait of openness felt better about themselves after viewing idealized images but worse about themselves after viewing the heavier images. Further, research suggests that when the target is seen as attainable, when people are focused on non-appearance dimensions of a target, or when they are primed with a self-improvement motive, viewers can have more positive affective responses to an attractive media target ( Joshi, Herman, & Polivy, 2004;Halliwell & Dittmar, 2005;Halliwell, Dittmar, & Orsborn, 2007;Knobloch-Westerwick & Romero, 2011;Lew et al, 2007).…”
Section: Social Comparison Media Exposure and Body Imagementioning
confidence: 99%